Gender bias in Islamic textbooks for Muslim children in Indonesia - Suwardi Suwardi; Sri Anitah W; Muhammad Akhyar; Asrowi Asrowi (IAIN Salatiga, 2017)
Textbook has a strong influence on the formation of children’s attitudes and value system. Therefore, Islamic textbooks as the main learning source for Muslim children in Indonesia need to consider the gender equality. This is very important to note, because feminists often view that Islam contains teachings of gender inequality. Islam places men in the higher position, while women are placed in the lower position. For example, men can be imam for women in prayer, but women cannot be imam for men. It is easier for children to learn textbook material presented in pictures. Therefore, the pictures presented in Islamic textbooks ideally do not contain gender bias. So, a research is needed to know if there is gender bias in the pictures presented in Islamic textbooks taught to Muslim children in Indonesia. To prove it, a literary research is conducted on the Islamic textbooks taught to the first grade Muslim student of Islamic Elementary School/ Madrasah Ibtidaiyah (MI) in Indonesia which includes pictures in their teaching materials. Islamic textbooks studied in the research include Fikih, Akidah Akhlak, and Arabic textbooks. The results of this study conclude that the pictures presented in Islamic textbooks taught in Muslim children in Indonesia contain gender bias. The man favor pictures are more than those of woman favor. Based on the conclusion, this study recommends an improvement of pictures presented in Islamic textbooks taught to Muslim children in Indonesia.